Regenerative Endodontic Treatment in Maxillary Central Incisor: A 6-month Case Report - Sumit Dash1, Debkant Jena1, Lora Mishra1, Satabadi Pattanaik2, Pratyaee Basu3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
The most important cause of pulpal necrosis was trauma during an eruption of the tooth, trauma causedelayed root formation, which leads to fracture of root. In recent advancements in the field of dentistry wecan convert non-vital teeth into vital once again by regenerative endodontic procedure. There are manyprocedures we can included in the regenerative are root canal revascularization, pulp implant, stem celltherapy, gene therapy and injectable scaffolds. In this case report we discuss the successful regenerativeendodontic treatment of necrotic permanent maxillary left central incisor. On clinical and radiographicexamination the large periapical defect in respected tooth end. After local anesthesia administration, rubberdam placed, access cavity preparation will be done with sterilization protocol, irrigation with the irrigationmaterial for the choice was 1.25% of sodium hypochlorite with saline after proper irrigation no filing will bedone at this point of time after this calcium hydroxide will be placed in the dry canal after 3 months follow,intraoral periapical radiograph shows less radiolucent area as compare to baseline radiograph and no visibleinflammatory sign seen in the surrounding tissue then filing will be done in the canal to induce bleedingafter visible bleeding visible in the canal after canal dry MTA will be placed. During the following periodthe patient as asymptomatic and after a 1-year x-ray the lesion was subsided and followed by root canaltreatment completion.